The praxeological curriculum as emancipatory interest of knowledge - Edgar Oswaldo Pineda Martínez; Paula Andrea Orozco Pineda (Corporación Universitaria Minuto de Dios, 2016)
With a view to present some understanding alternatives in front of the praxeological curriculum discussion, this article looks forward in the opening of horizons of sense about the relationship between curriculum, praxeology, praxis and pedagogical learning over the higher education. In a first step, it has to be done an approximation to the main sceneries that determine in any form the possibilities to the praxeological curriculum from the interdiscipline and the subjectivity in the higher education exercise. Then, in a second step, it is presented the praxeological curriculum with a possibility of transformation and a pedagogical practice re-significance since the knowledge interest's concepts of Habermas and from the Grundy'scurriculum type. Forward, it is presented a comparison between the concepts of Habermas and Grundy about the curriculum and the knowledge interest, the praxeological curriculum and its thoughtfulnesses, knowledges and universitarian teacher's notions. Finally, it is presented the need of formation since the human being, in terms of the social education, the popular education and the praxeology, as a fundamental option of the praxeological curriculum.